PRINSIP DEMOKRATISASI SASTRA AHMED FADEL SHABLOUL PADA SASTRA DIGITAL WATTPAD - Nur Amalia, Annisa Jati (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This research discusses the phenomenon of literary democratisation in the context of digital literary criticism, which has changed the traditional landscape in the process of creating, distributing and evaluating literary works. Literary democratisation refers to the open access and participation of various layers of society in the world of literature, supported by digital technology. This research aims to identify the role of digital literary criticism as an inclusive medium in supporting the engagement of the community of readers and writers, and analyse its impact on the development of literary aesthetics. Using a qualitative-descriptive approach, this research utilises secondary data in the form of journal articles, books, and relevant digital literary works. The results show that digital literary criticism not only expands the discussion space through online platforms such as blogs, social media, and literacy forums, but also creates a new culture of literary appreciation that is more interactive and inclusive. Nonetheless, challenges such as community fragmentation, validity of criticism, and loss of quality control are still important issues. This research confirms that digital literary criticism has great potential to support the democratisation of literature, while encouraging the development of values of inclusivity, diversity and innovation in the world of literature.